2010
DOI: 10.1093/jat/34.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Liquid Chromatography-Tandem Mass Spectrometry Ion-Trap Technique for the Simultaneous Determination of Thirteen Anticoagulant Rodenticides, Drugs, or Natural Products

Abstract: The purpose of this study was to develop and validate a liquid chromatography-tandem mass spectrometry method for the identification and quantification of anticoagulant (anti-vitamin K or AVK) compounds, including rodenticides, drugs, and natural products because no published method could be found. The proposed method is based on ion-trap technology with electrospray ionization (ESI) and multiple reaction monitoring (MRM) technique. Each AVK is identified by means of its retention time, precursor ion, and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Although one review of anticoagulant rodenticide intoxication determined that affected animals had a poor prognosis, a more recent review of 123 cases where toxicology screening was performed reported dogs presenting with signs of coagulopathy attributed to anticoagulant rodenticide had a better prognosis (98.7% survival rate) than dogs presenting with similar clinical signs that were negative for anticoagulant rodenticide exposure (62.5% survival rate) . As duration of treatment is dependent on dose and type of anticoagulant rodenticide ingested, toxicology screenings for specific anticoagulant rodenticides may be beneficial in determining prognosis and bolstering an owner's willingness to treat . On‐site toxicology testing for anticoagulant rodenticide was not performed in the cases reported here; however, all cases had complete resolution of clinical signs after completing a 30 day course of oral vitamin K 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one review of anticoagulant rodenticide intoxication determined that affected animals had a poor prognosis, a more recent review of 123 cases where toxicology screening was performed reported dogs presenting with signs of coagulopathy attributed to anticoagulant rodenticide had a better prognosis (98.7% survival rate) than dogs presenting with similar clinical signs that were negative for anticoagulant rodenticide exposure (62.5% survival rate) . As duration of treatment is dependent on dose and type of anticoagulant rodenticide ingested, toxicology screenings for specific anticoagulant rodenticides may be beneficial in determining prognosis and bolstering an owner's willingness to treat . On‐site toxicology testing for anticoagulant rodenticide was not performed in the cases reported here; however, all cases had complete resolution of clinical signs after completing a 30 day course of oral vitamin K 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Rodent resistance to the first‐generation anticoagulant rodenticide warfarin prompted the development of more potent second‐generation formulations . Unlike first‐generation rodenticides, the second‐generation formulations are effective after a single ingestion in target species …”
Section: Introductionmentioning
confidence: 99%
“…AVK analysis is conducted on either blood or liver samples using high performance liquid chromatography techniques with fluorescence and UV detection or mass spectrometry detection (for confirmatory purposes). [6][7][8] The technique has been developed to monitor suspected cases for synthetic anticoagulant rodenticides (eight substances available in France) as well as some natural anticoagulants (ferulenol and dicoumarol). All incoming cases are ''suspected poisoning'', while only those with detection of a given anticoagulant with consistent clinical/pathological findings will be classified as ''poisoning'' cases.…”
Section: Wildlife Toxicovigilance Schemementioning
confidence: 99%
“…Anticoagulant rodenticides (coumatetralyl, difenacoum, brodifacoum, bromadiolone, warfarin, chlorophacinone, coumafuryl, diphacinone, coumachlor, difethialone, flocoumafen and dicoumarol) were quantitated from biological samples such as plasma, serum, blood, liver and hair by various techniques of LC-MS. Electrospray ionization (ESI) in negative mode was extensively used for ionization of analytes. In reported LC-MS and LC-MS/MS methods, elution was performed by isocratic [20,21,26,30] as well as by gradient manner [18,19,[22][23][24][25][27][28][29][31][32][33]. The MS parameters used in these methods were capillary voltage (2.5-3.0 kV), capillary exit voltage (À135 to À205 V), drying temperature (325-350 8C), high purity (99.999%) dry nitrogen gas ( [29] performed using helium as collision gas at a pressure of 1.22 Â 10 À5 mbar [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%
“…This method can be considered more reliable and selective based on reported validation parameters (Table 3). Thirteen rodenticides in plasma were determined using LC-MS/MS with ion trap technique [27]. This method has advantage of enhanced specificity with the use of an ion trap instrument to simultaneously collect both full scan MS and tandem MS data.…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%